Efficacy and Safety of Traditional Chinese Medicine Injections for Heart Failure With Reduced Ejection Fraction: A Bayesian Network Meta-Analysis of Randomized Controlled Trials - Lin, Shanshan; Shi, Qingyang; Ge, Zhao; Liu, Yangxi; Cao, Yawen; Yang, Ying; Zhao, Zhiqiang; Bi, Yingfei; Hou, Yazhu; Wang, Shuai; Wang, Xianliang; Mao, Jingyuan (Frontiers in Pharmacology, 2021)
Background: Heart failure (HF), as an important issue in global public health, has brought a heavy economic burden. Traditional Chinese medicine injections (TCMIs) have significant effects on heart failure with reduced ejection fraction (HFrEF). However, it is difficult for clinicians to identify the differences in clinical efficacy and safety of various TCMIs. The purpose of this study is to compare the efficacy and safety of various TCMIs for treating HFrEF by conducting a Bayesian network meta-analysis (NMA) and to further provide references for clinical decision-making. Methods: The clinical randomized controlled trials (RCTs) of TCMIs for treating HFrEF were searched in seven database from inception to December 22, 2020. The Cochrane collaboration’s tool was used to assess the risk of bias. NMA was performed in a Bayesian hierarchical framework. The surface under the cumulative ranking curve (SUCRA), the multi-dimensional efficacy analysis, the comparison-adjusted funnel plot, and the node-splitting analysis were conducted using R software. Results: A total of 102 eligible RCTs involving 8,719 HFrEF patients and 6 TCMIs were included. TCMIs include Huangqi injection (HQ) also called Astragalus injection, Shenfu injection (SF), Shengmai injection (SGM), Shenmai injection (SM), Xinmailong injection (XML), and Yiqifumai lyophilized injection (YQFM). The results of NMA and SUCRA showed that with conventional pharmacotherapy (CP) as a common control, in terms of clinical efficacy, CP+XML was most effective in NYHA cardiac functional classification efficiency, 6MWT, LVEDD, BNP, and NT pro-BNP; the CP+YQFM was most effective in LVEF; the CP+SM was most effective in LVESD and CO; the CP+HQ was most effective in SV; the CP+SF was most effective in MLHFQ. The overall evaluation of CP+XML is relatively good. In terms of safety, there was no significant difference between CP+TCMIs and CP. Conclusion: Based on this Bayesian network meta-analysis results, the combination of qualified TCMIs and CP may be more effective for HFrEF patients than CP alone, and CT+XML and CT+SM may be one of the potential optimal treatments. The safety of these TCMIs needs to be further observed. However, due to some limitations, the conclusions of the study need to be verified by more large-sample, double-blind, multi-center RCTs.